Knowledge, attitudes and practices of contraception among high school students in Tswaing sub-district, North-West Province. - Onyensoh, O. O. C. (University of Limpopo (Medunsa Campus), 2011)
Aim and objectives Challenged by the high incidence of teenage pregnancy and sexually transmitted infections observed among high school students who were attending antenatal care at the clinics in Tswaing Sub-district. The researcher conducted this study to determine the knowledge, attitudes and practices of contraception among high school learners and establish whether the demographic characteristics of the students influenced their knowledge, attitudes and practices towards contraception. Design This study was a cross-sectional descriptive quantitative study. It was conducted among 231 learners who were aged 16 years and above, male and female, between grades 10 and 12. Systematic sampling was employed to select 33 students from 7 high schools selected by random probability sampling technique in Tswaing Sub-district who completed confidential, anonymous self-administrated questionnaires. The questionnaires were in English, Afrikaans and Setswana, so as to ensure clarity and accurate understanding of the content and hence the questionnaire was self-administered in the language of preference for each learner. Data were entered and analyzed using SPSS for windows version 17. A chi-square test was performed to determine the association between predictor's variables and knowledge. A p-value ofless than 0.05 at 95% CI was taken for statistical significance. Results More males 70 % and 60 % of the females indicated that they had a boyfriend or girlfriend. More males (50.3%) than females (49.7%) indicated that they had engaged in sexual intercourse. The average age of first sexual intercourse was 14.9 years for the males and 15.4 years for the females. The modal age for first intercourse for male was below 13 years and 15.4 years for the females. The most common contraceptive used among the males was a condom (89.8%) and among females, it was the combined injectable contraceptives (49.4%). Males (63.6%) and females (68.8%) thought it easy to access contraception. There was a high rate of unprotected sexual activity among the learners, with 34.1 % of the males and 42.1 % of the females' indicated that they had had sex without contraception. Most of the learners obtained contraceptive information from their parents 98 [33%] male, 70 [53.8%] female). The preferred source of information for the male learners was a doctor 59 [59%], and the preferred source of con1raceptive information for the female learners was their parents 57 [43%]. 54 (57.4%) of the males and 75.4% of the 84 female learners indicated that their parents had discussed contraception with them. 64.2% of the males and 68.5% of the females claimed that they were satisfied with the information they received about contraception from their parents. All the learners had the knowledge that condoms can prevent sexually 1ransmitted infections and that a condom cannot be used more than once, with a p< 0.05 and their response according to gender and age, all schools had more than 60% participants. Forty-three percent of the learners in all schools who lived with both parents had the knowledge that condoms can prevent sexually transmitted infections and condom cannot be used more than once, p< 0.05. Among the female learners, only 79 [60.8%] knew that conception could take place if they missed taking their con1raceptive pill once. 51 [39.2%] said that conception could not take place if they had missed taking the pill once. More than 90% learners wanted information on contraception from their primary health care providers. Conclusion This study showed that senior learners had a good knowledge about basic contraception. The high level of sexual activity, early sexual initiation and low contraceptive use put these adolescents at risk of pregnancy and sexually transmitted infections. They indicated that they needed more information on sexuality and contraception from their primary health care providers especially from their doctors. Adolescents should be encouraged to ask about contraception and sexual health at the clinics, and all health workers; nurses and doctors, who consult must see every encounter as an opportunity for health education and counseling in reproductive health
Thesis (M Med (Family Medicine)) -- University of Limpopo, 2011.
Keywords: Contraception; Contraceptive devices